Strict U-Ideals and U-Summands in Banach Spaces - Abrahamsen, Trond A. (MATHEMATICA SCANDINAVICA, 2014)
For a strict u-ideal $X$ in a Banach space $Y$ we show that the set of points in the dual unit ball $B_{X^{*}}$, strongly exposed by points in the range $\it TY$ of the unconditional extension operator $T$ from $Y$ into the bidual $X^{**}$ of $X$, is contained in the weak$^{*}$ denting points in $B_{X^{*}}$. We also prove that a u-embedded space is a u-summand if and only if it contains no copy of $c_0$ if and only if it is weakly sequentially complete.